Les mots pour traduire l'art : la parole leclézienne - Rey Mimoso-Ruiz, Bernadette (Verbum – Analecta Neolatina, 2013)
When Le Clézio speaks about artworks, he does not follow the method of the observing theorists and art critics, but goes into an opposite direction: the narrative is dominant while the description conjures up impulses that have created the artwork and provide the key to reading. The description supplementing the narrative digresses, then launches the story, so that the imagination, beliefs and feelings are unified inside the work of art evoked: thus is born the poetic nature of the depicted subjects which transform the artwork into the metaphor of the invisible.